Analysis of Cash Management at Baing Yusuf Grand Mosque, Purwakarta Regency (Judging from the Management Aspect and Its Allocation) - Dedah Raudatul Jannah (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2019)
This study is an Analysis of the Cash Management of the Baing Yusuf Great Mosque in Purwakarta Regency (Judging from the Management Aspect and Its Allocation). researchers are interested in conducting this research because there are still many problems in the management of mosque cash funds such as the construction of mosques that have not been completed for years, mosque administrators do not have more money to pay priests, preachers or muezzins, even mosques do not have janitors because of the lack of mosque cash funds. In addition, many mosque facilities are still lacking such as a broken fan, only a few ablutions, no mosque management rooms, and so on. Plus there are still many mosques that lack funds and even deficits. The purpose of this study is to find out about the source of receipt of the Great Mosque Baing Yusuf Purwakarta cash fund, the cash management system of the Great Mosque of Baing Yusuf Purwakarta, and to find out about the cash allocation system in the Great Mosque of Baing Yusuf Purwakarta. The method of collecting data in this study is by interview, observation and documentation. The data sources used are primary and secondary data sources. The data analysis used a Descriptive Qualitative approach by reviewing the cash management system of the Great Mosque of Baing Yusuf Purwakarta. The results of this study can be concluded that the source of cash receipts of the Great Mosque of Baing Yusuf comes from the charity box of the pilgrims. The management of cash funds is already good because the financial circulation is clear and transparent and the allocation of funds is clear to pay the wages of priests, preachers, marbots, muezzins and so forth.